Perbandingan kemampuan pemecahan masalah matematik peserta didik antara yang menggunakan model problem based learning (PBL) dengan problem solving - Sinta Silvia; Nani Ratnaningsih (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
This study aims to compare mathematical problem-solving ability among learners who learned with problem-based learning model (PBL) and problem-solving. The study also aims to determine the thinking process of learners in the problem-solving. The study was using an experimental method. The population was all students of class VIII SMP Negeri 13 Kota Tasikmalaya. The samples were selected two classes by cluster random sampling, first class (VIII-E) was learned by using PBL model and second class (VIII-J) was learned by using problem-solving. Data collection techniques use mathematical problem-solving tests. The data were analyzed by t-test of two difference means. The study concludes that the mathematical problem-solving ability of learners who learned with PBL model better than that learned with a problem-solving model. The conceptual thinking process in the PBL class was owned by high-ability learners, while in the problem-solving class was owned by high and middle-ability learners. The semi-conceptual thinking process of the PBL class was owned by moderate and low-ability learners, while the problem-solving class was owned by moderate-ability learners. Computational thinking processes in PBL classes and problem-solving one were owned by low-ability learners.Keywords: problem-based learning (PBL), problem-solving, mathematical problem-solving ability, thinking process.